An exploration of the social classes among settlers in Bago Oshiro - Clamonte, Valeriano A. Jr
The objectives of this study are: (1) to describe the general conditions of social stratification in the community; (2) to identify the factors, dimensions, and indicators of stratification in Bago Oshiro; (3) to arrive at a conclusion on the basis of how the community's stratification is maintained, sustained and changed. The study involved 120 households from twelve different puroks in Barangay Bago Oshiro. An interview schedule was used to gather data. The study reveals that the average age of the respondents is 45.5 years for both husbands and wives. Many of the settlers have their region of origins in the Visayas and Luzon. Majority of them hails from Cebu and Bohol, and parts of Luzon especially the Ilocos region. Most of the respondents were already born in Bago Oshiro. Some 95 percent are Catholics. The average number of children per household is four but other extended family members were also present. The extended nature of the household is characterized by in-laws and unmarried brothers/ sisters of the couple. Neolocal type of residence is reported by a majority of the respondents these households live mostly on decent housing made of concrete and wood. The average educational attainment of the respondents is high school graduate for both husbands and wives. Yet quite a number of households have espouses earned college degrees. An average number of 3.5 children per households attended school where 62.5 percent went to public schools. Majority of the children attended public institutions while there are also some went to private schools. The average annual income per household was P96, 750.50. Some 57.5 percent reportedly have two or more sources of income. The income incurred by the household comes mostly from salaries/ wages of the employed respondents. Income from farmers is meager due to the slumping copra price in the market. Political power and influence almost exclusively rest on member of the legal- rational authority exercised by the barangay council. Some big businessmen, officials of government bureaus and leaders of farmers' associational are among the very few that enjoy high status on this regard. Social stratification in Barangay Bago Oshiro reveals the importance of looking into it in different levels. Socially, residents have almost a common place of region of origin. The family size although quite large at a national average level seems to be medium size for a rural setting. Living standards looked to be stable also except for those farmers who were heavily affected by the collapsing coconut market. Education and income levels come hand in hand as college degree holders earn stable incomes. Higher income and households with spouses having higher education also have smaller family size. Political participation however, remains low except during election periods where most of the respondents reportedly vote. The educated members in the community mostly occupy status positions while farmers' also involve themselves in leadership to some non- government organizations/ or people's organizations like farmers' associations.